Efficiency potential of indirectly heated solar reforming with open volumetric solar receiver. (5th August 2015) - von Storch, Henrik; Stadler, Hannes; Roeb, Martin; Hoffschmidt, Bernhard
Abstract: In solar reforming, the heating value of natural gas is increased by utilization of concentrated solar radiation. Hence, it is a process for storing solar energy in a stable and transportable form that also permits further conversion into liquid fuels like methanol. The feasibility of solar reforming is proved. However, its overall process efficiency potential has not been studied systematically. In this work, an indirectly heated solar reforming process with air as heat transfer fluid is designed and modelled to produce syngas suitable for subsequent methanol synthesis. For provision of solar high temperature heat, an open volumetric receiver is implemented into the process model and the overall performance is investigated. Results show the paramount significance of the air return ratio of the receiver and its ability to achieve high efficiencies at temperatures above 850 °C. For realistic air return ratios, design point process efficiencies of 19% can be achieved, for an increased air return ratio, values up to 23% are feasible. The determined corresponding annual efficiencies are 12% and 14% respectively. Considering its relative technical simplicity this makes indirectly heated solar reforming a promising technology to overcome the current limitations of solar energy in the medium term. Highlights: A process for solar reforming of natural gas is proposed. A process model is developed to determine process efficiency. Several process parameters are investigated and the process is optimized to reach high efficiencies. The process achieves promising efficiencies. The solar receiver is the crucial process unit for further improvement of process performance.